RESEARCH INTO MEDICAL REFERRALS FOR SENSORY INTEGRATION TREATMENTS (REMUNOM, 2024)
In this study, we sought to investigate medical referrals for sensory integration by occupational therapists. The methodology used was an exploratory and descriptive convenience approach, aiming to collect data through surveys distributed via social media and WhatsApp. The basis was the "snowball sampling" technique, a non-probabilistic sampling method used in qualitative research, especially when accessing specific or hard-to-reach populations.  Results: Nine (9) doctors participated in the research, including psychiatrists, neurologists, and pediatricians, who completed the online questionnaire. It was found that most participants treat patients across all age groups, with only 2% working exclusively with children under 5 years old. Regarding the understanding of the sensory integration method and Ayres Sensory Integration, it was observed that 55.6% of participants consider them similar approaches. From the qualitative perspective, a lack of discernment among doctors was noted regarding the differences between the two techniques, despite directly referring patients for sensory integration treatment without requesting a prior evaluation by an occupational therapist— a professional qualified to determine the necessity and frequency of this approach. Additionally, the late diagnosis of Autism Spectrum Disorder (ASD) reduces early intervention, allowing symptoms to progress and delaying appropriate care.  It was concluded that Sensory Integration Theory and Ayres Sensory Integration are similar; however, the latter is patented in the United States, making in-person training less accessible. Furthermore, doctors should better understand sensory integration to first request an anamnesis before referring patients for treatment.